INTERNALISASI NILAI-NILAI ISLAMI OLEH GURU PENDIDIKAN AGAMA ISLAM MELALUI METODE PEMBIASAAN DI MADRASAH TSANAWIYAHAL-UKHUWWAH KECAMATAN BANJANG - Rahmadaniyati Rahmadaniyati; Abdul Wahab Syakhrani (CV. Adiba Aisha Amira, 2025)
In this era of rapid development, moral and ethical values are often tested because there are still many behaviours that indicate that Islamic religious education has not been successful in educating students to develop ethics and morals. Therefore, Islamic religious education plays a very important role in internalising Islamic values so that students can understand, appreciate, and practise Islamic values in their daily lives. This study aims to describe how Islamic values are internalised by Islamic religious education teachers through the habit formation method. The research was conducted at MTs Al-Ukhuwwah in Banjang District. The research subjects were Islamic religious education teachers with informants consisting of students, the head of the religious affairs department, the school principal, and administrative staff. In collecting data, the author used observation, interviews, and documentation techniques. The author also used qualitative data analysis techniques with a descriptive method. Meanwhile, data validity was checked using triangulation. The results of the study indicate that the internalisation of Islamic values by Islamic education teachers through the habituation method has been implemented at MTs Al-Ukhuwwah in Banjang District. The internalisation process involves several stages. First, the value transformation stage, which involves informing or communicating what values are good or bad. Second, the value transaction stage, which involves guiding students towards the values that have been communicated. Third, the trans-internalisation stage, which involves becoming a role model or good example. The forms of habit formation in the internalisation of Islamic values include activities that occur both within and outside the learning process, such as shaking hands and greeting others, praying before and after lessons, reciting the Qur'an, performing Dhuha prayers in congregation, performing Zuhr prayers in congregation, religious activities, extracurricular activities, and commemorations of important Islamic days. With this habit-forming method, the values of faith, morals, and worship can be realised well with the support and role of Islamic education teachers in guiding and directing the personalities of students to be better, so that students not only gain general knowledge but also religious knowledge that is embedded in themselves. The factors that hinder internalisation are the influence of the environment, moral and ethical decay, and the influence of technology. Meanwhile, the supporting factors are advice from teachers, motivation and rewards, supervision, and punishment.